Tras la restauración del puente que une a la teoría de la ciencia con la teoría general del conocimiento: un a propuesta de epistemología jurídica que vincula al derecho con la justicia (2012)
This article presents an alternative in the way ofconceiving theepistemological legal, which seeks to contribute tothe restoration of the existingbridge between scientific theory and the theory ofknowledge. Restoration,because the concept of epistemology used since the19th century mentioned,predominantly a theory of particular Sciences, generating a substitution of thegeneral theory of knowledge by the general theory of science. This phenomenonhad significant consequences for science as law, which can become spectacularlyevident in many of modern theories of law. One of these effects - perhaps the mostimportant-, has been the create a gap between law and justice, or in the not correctintellection of its relations